Strain-life fatigue assessment of scanned weld geometries considering notch effects. (15th December 2019) - Niederwanger, A.; Ladinek, M.; Lener, G.
Highlights: Evaluation of established strain-life concept parameter estimation methods applied to welded structures. An adapted version of the strain-life approach for weldments based on comparison to other concepts and parameter fitting is proposed. Verification of the applicability of Liu's statistical size effects for welded components, and determination of the Weibull coefficient. Superior fatigue life prediction accuracy compared to state-of-the-art concepts is observed. Abstract: Fatigue failure is one of the most encountered problems with dynamically loaded engineering structures. A sophisticated assessment approach to tackle fatigue is the strain-life concept, which enables the consideration of many different aspects, such as mean stress effect, size effect, surface roughness, or net section yielding. Originally developed for base material, the present work aims to enable its reasonable application to welded components. However, there are two significant problems. On the one hand, the strain-life approach does not provide any recommendations on weld modeling, which means that the geometry of each assessed weld has to be known. On the other hand, the majority of the available material properties correspond to base material. Especially conventional approximation formulae, which relate strain-life fatigue parameters to more accessible data, such as static properties or hardness measurements, predict poor results if applied to weld material. The first issue is tackled by incorporating the real weld geometry into the assessment through 3D laser-scanning. The latter is addressed by proposing fatigue properties for welded components. After showing that conventional approximation methods do not accurately describe the fatigue behavior of weldments, thoughts on adjusting the slope of the strain-life curve, based on comparison to other fatigue approaches and least-squares fitting using experimental data, are presented. Additionally, recommendations are provided on the statistical size effect, namely the highly stressed area and the Weibull exponent. By using the proposed parameters for the strain-life concept, significant improvement in terms of prediction accuracy compared to conventional parameter estimation methods was observed. The proposed model is able to explain more scatter of experimentally determined fatigue lives than state-of-the-art stress-life fatigue models for welded components.